1, 4, 7‐Triazacyclononane (tacn) with N, N′‐bridging methylene‐bis(phosphinic acid) group and its complexes. Issue 12 (7th May 2021) - Pazderová, Lucia; Kubíček, Vojtěch; Kotek, Jan; Hermann, Petr
Abstract: A bicyclic ligand, 1, 4, 7‐triazacyclononane 1, 4‐bridged with methylene‐bis(phosphinate) and bearing benzyl substituent on the remaining amino group, was synthesized from N ‐benzyl‐tacn and CH2 (PO2 H2 )2 by two sequential Mannich‐type reactions in a high yield. Basicity of the macrocycle is high (p K 1 =12.25). Complexes with Cu II and Ni II ions show dimeric structures in the solid state. The structures exhibit distorted octahedral environment with two ring amino groups from one molecule and two oxygen atoms of chelating bis(phosphinate) anion from the other molecule in the equatorial plane, and with the apical positions occupied by the remaining macrocycle amino group and by one of the phosphinate oxygen atoms. The metal ions in the dimers are additionally bridged by one phosphinate group. Stability of the Cu II complex is more than ten orders of magnitude lower than that of the [Cu(nota)] − complex due to a different number and different nature of the pendant arms, and inappropriate arrangement of donor atoms in the ligand bicyclic structure. Rigidity of the short P−C−P chain of the geminal methylene‐bis(phosphinate) does not allow simultaneous coordination of both phosphinate groups and the ring amines to the same metal ion. The low solubility of Ni II and Zn II complexes disabled determination of their stability constants. Abstract :